2003
DOI: 10.1097/00008390-200304000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The problem of false-positive diagnosis in melanoma screening

Abstract: The predictive value of melanoma diagnosis made by visual examination during pigmented lesion screening is low. This creates the problem of false-positive diagnoses, which lead to unnecessary treatment and scarring. The purpose of this study was to evaluate the impact of dermoscopy (epiluminescence microscopy, dermatoscopy) on the false-positive rate in the routine melanoma screening activity of a pigmented lesion clinic (PLC). In a series of 133 subjects consecutively referred to the PLC, lesions defined as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 16 publications
2
58
1
1
Order By: Relevance
“…Dermoscopy reduced the number of excisions considerably (42%), which is in agreement with other studies (7)(8)(9). In a randomized study Carli et al (7) found that 38% less excisions were performed in the dermoscopy study-arm compared with the NEE arm.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Dermoscopy reduced the number of excisions considerably (42%), which is in agreement with other studies (7)(8)(9). In a randomized study Carli et al (7) found that 38% less excisions were performed in the dermoscopy study-arm compared with the NEE arm.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have shown that dermoscopy is better than naked eye examination (NEE) at discriminating melanoma from benign pigmented lesions (4)(5)(6). However, few studies have investigated the effect of dermoscopy in everyday clinical practice by studying how it guides management decisions (7)(8)(9)(10). The beneficial effect of dermoscopy ultimately depends on how it improves the ability to determine whether lesions need to undergo biopsy (8,(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…From a meta-analysis of nine level II diagnostic studies subject to varying degrees of verification bias performed prospectively in a clinical setting the diagnostic accuracy for melanoma, as expressed by the relative diagnostic odds ratio, was 15.6 (95 % CI 2.9-83.7) times higher for dermoscopy compared with naked eye examination [26][27][28][29][30][31][32][33][34][35][36]." ([19] p. 29).…”
Section: Level Of Evidence 1bmentioning
confidence: 99%
“…For this reason, and based on other evidence [39], some formal training in dermoscopy is required to achieve improvement in diagnostic accuracy." ([19], p. [29][30].…”
Section: M1c Distant Metastasis(es) At Other Location or Normalmentioning
confidence: 99%
“…10 However, to show that dermoscopy is more sensitive than clinical examination in detecting melanomas is problematic. The sensitivity of a dermatologist in detecting a melanoma is very high.…”
Section: Important Clinical Questions That Cannot Be Answered In Smalmentioning
confidence: 99%